Independent Learning-Independent Campus Policy Innovation at State Aliyah Madrasas - Dewi Agung Margaretha; Ainun Nadlif; Anita Puji Astutik; Sabbir Hasan (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2023)
Since the Minister of Education and Culture Nadiem Makarim put forward the idea of independent learning, there has been much talk about it in the world of education including the campus idea for independent learning. This concept is an attempt to deal with the changing times, so how is the concept of an independent learning campus that was coined by the Minister of Education and Culture, Mr. Nadiem Makarim, the purpose of the researcher here is to explain how the concept and application of MBKM are in Madrasah Aliyah and what is the problem in Madrasah The current Aliyah Negeri requires a change in the concept of the Madrasah Aliyah Negeri for the better. This article uses a type of qualitative research with a descriptive approach. The results of the study show that the implementation of the Sidoarjo State Madrasah Aliyah towards the independent learning policy about 4 concepts that PAI teachers at the State Aliyah Madrasah feel the advantages of the Free Learning concept where learning can proceed as intended, while their students can also feel the advantages of the Merdeka concept. Learning is that it is easier to understand the material conveyed by the teacher as well as students can be more expressive in the classroom so that the learning process is carried out more fun. Teachers also always hold weekly deliberations to find out the progress of the 4 Free Learning concepts.